Seeing the Outer Edge of the Infant Type Ia Supernova 2024epr in the Optical and Near Infrared - W. B. Hoogendam; D. O. Jones; C. Ashall; B. J. Shappee; R. J. Foley; M. A. Tucker; M. E. Huber; K. Auchettl; D. D. Desai; A. Do; J. T. Hinkle; S. Romagnoli; et al. (The Open Journal of Astrophysics)
We present optical-to-near-infrared (NIR) photometry and spectroscopy of the Type Ia supernova (SN~Ia) 2024epr, including NIR spectra observed within two days of first light. The early-time optical spectra show strong, high-velocity Ca and Si features near rarely-observed velocities at $\sim$0.1$c$, and the NIR spectra show a \CI\ "knee.'' Despite early-time, high-velocity features, SN~2024epr evolves into a normal SN~Ia, albeit with stronger peak-light Ca absorption than other SNe~Ia with the same light curve shape. Although we infer a normal decline rate, $Δ m_{15}(B)=1.09±0.12$~mag, from the light-curve rise, SN~2024epr is a Branch "cool'' object and has red early-time colors ($g-r≈0.15$~mag at $-10$~days). The high velocities point to a density enhancement in the outer layers of the explosion, predicted by some models, but thick-shell He-detonation models do not match the smoothly rising light curve or apparent lack of He in our early-time NIR spectra. No current models (e.g., delayed detonation or thin He shell double detonation) appear to reproduce all observed properties, particularly the unusual early-time colors. Such constraints are only possible for SN~2024epr from the earliest optical and NIR observations, highlighting their importance for constraining SN~Ia models. Finally, we identify several literature SNe~Ia with intermediate mass elements at $\sim$30\,000~km~s$^{-1}$ within days after the explosion that evolve into otherwise normal SNe~Ia at peak light, suggesting the early-time spectra of SNe~Ia may hide a broad diversity of observational characteristics.